The Effectiveness of Extensive Reading on EFL Learners’ Vocabulary Learning: Incidental versus Intentional Learning - Teng, Feng (BELT - Brazilian English Language Teaching Journal, 2015)
Forty-six students majoring in business English volunteered to take part in an extensive reading program. The learners were divided into two groups: EG, the experimental group, received instruction in methods of extensive reading plus explicit output-pushed activities, and CG, the control group, received instruction in methods of extensive reading only. This study measured the effects of extensive reading on EFL vocabulary learning, as well as the effects of the two different instruction methods on learning receptive and productive vocabulary for the 46 learners of different vocabulary size. The research found that (a) both the two instructional methods resulted in significant gains in learners’ receptive and productive vocabulary knowledge, but the combination of the incidental and intentional learning instruction yields greater vocabulary gains; (b) around 60 % of receptive vocabulary is understood productively; and (c) students’ vocabulary size plays a decisive role in acquiring the receptive and productive aspect of vocabulary knowledge.